Enhancing Primary Health Care through Interprofessional education: Insights from a Training Workshop - Milani, Chiara; Naldini, Giulia; Occhini, Giulia; Pontalti, Irene; Baggiani, Lorenzo; Nerattini, Marco; Lorini, Chiara; Turco, Lucia; Bonaccorsi, Guglielmo; PHC-W working Group,; Del Riccio, Marco (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Strengthening primary care services with a focus on comprehensive Primary Health Care principles necessitates collaborative work practices within interprofessional teams. In Italy, the Local Health District of Florence embodies a comprehensive Primary Health Care-inspired model of primary care, prominently featuring the House of Community concept. This work presents findings and insights from a multidisciplinary, interprofessional education activity tailored for healthcare professionals, researchers, and students actively participating in the primary care reorganization.Methods. The activity was structured using a four-phase learning model (imaginative, analytical, common sense, and dynamic), aligning with four distinct activities (brainstorming, lecture, case study, and group project).Results. Key themes that emerged encompassed the significance of nurturing relationships among team members, the aspiration for an inclusive work environment, the vital role of community engagement and collaboration across various services, disciplines, and sectors beyond healthcare.Discussion. These themes highlight the essential attributes of successful primary care practices built on the principles of comprehensive Primary Health Care. Throughout the innovation process of primary care services, interprofessional education training events emerged as indispensable components for bolstering implementation and ensuring sustainability. This study underscores the crucial role of interprofessional education in bridging the gap between theoretical constructs and practical application, emphasizing that comprehensive Primary Healthcare principles find tangible manifestation in real-world scenarios.